Suppressed radiation-induced dynamic recrystallization in CrFeCoNiCu high-entropy alloy. (1st January 2021) - Kim, Jinyeon; Lim, Jong Wook; Kim, Joon Kon; Kim, Do Hyang; Park, Eun Soo; Chang, Hye Jung
Abstract: We report a map of irradiation-induced recrystallization and polygonization in a CrFeCoNiCu high-entropy alloy obtained by a precession electron diffraction technique. This orientation map enables the visualization of depth-dependent recrystallization at a glance and reveals the effects of irradiation dose and material entropy. Discontinuous dynamic recrystallization preferentially occurs near the surface, where the irradiation dose is low, but radiation-enhanced diffusion dominantly occurs leading to dislocation climb even at room temperature. Interestingly, in the high-entropy phase with a relatively low stacking fault energy, discontinuous dynamic recrystallizastion is suppressed due to the lower stored energy and grain boundary diffusivity compared low-entropy one. Graphical abstract: Image, graphical abstract